Highly regioselective dehexanoylation in fully hexanoylated flavonoids. Issue 50 (12th December 2018) - Zheng, Zhiwei; Han, Ziyi; Cai, Li; Zhou, Dandan; Chavis, Bryson R.; Li, Changsheng; Sui, Qiang; Jiang, Kaiyuan; Gao, Qi
Graphical abstract: Highlights: A hexanoyl-based protection strategy for flavonoids with broad substrate scope. Highly regioselective deprotection afforded various 7-hydroxyl flavonoids. A comparison between dehexanoylation and deacetylation. Phase-transfer-catalyzed glycosylation resulted in flavonoid 7- O -glycosides. Abstract: Highly selective removal of the 7- O -hexanoyl group in fully hexanoylated flavones, isoflavones, flavanone, and flavonol was achieved under mild conditions using K2 CO3 in a 1:1 mixture of CH3 OH–CH2 Cl2 . The resulting 7-OH flavonoids are valuable intermediates for the synthesis of flavonoid 7- O -glycosides via phase-transfer-catalyzed (PTC) glycosylation.